Prevalence of panton-Valentine leukocidin and toxic shock syndrome toxin-1 genes in methicillin-resistant Staphylococcus aureus isolated from nose of restaurant workers in Kirkuk city - Najdat Bahjat Mahdi (Wolters Kluwer Medknow Publications, 2023)
Staphylococcus aureus resides naturally in the nasal cavity of healthy individuals, including those working in restaurants, so they may be a source for spreading this bacterium to restaurant customers directly or indirectly through cooked meals. This bacterium has several virulence factors enabling it to cause many diseases in different parts of the body. It has also the capability to resist conventional antibiotics including methicillin. To investigate methicillin-resistant S. aureus (MRSA), 170 nasal swabs were collected from food preparation workers in 30 restaurants (5-6 workers in each restaurant) in Kirkuk city. After collection, the samples were directly transferred to the laboratory and cultured on selective media like mannitol salt agar (MSA). Microbiological examination including morphological, biochemical, and confirmatory tests showed that 24/170 of collected samples were positive for S. aureus with a rate of 14.12%. Among 24 isolates, 20 (83.3%) belonged to MRSA. All isolates were resistant to oxacillin and penicillin (100%), whereas sensitive to other antibiotics (gentamicin, chloramphenicol, and rifampicin). Polymerase chain reaction exhibited that 13 (65%) of MRSA isolates have toxic shock syndrome toxin-1 gene and only 4 (20%) have Panton-Valentine leukocidin gene.